Enhancement of synaptic excitation by GABAA receptor antagonists in rat embryonic midbrain culture - Rohrbacher, Jutta; Sauer, Katja; Lewen, Andrea; Misgeld, Ulrich (Journal of neurophysiology, 1998)
Rohrbacher, Jutta, Katja Sauer, Andrea Lewen, and Ulrich Misgeld. Enhancement of synaptic excitation by GABAA receptor antagonists in rat embryonic midbrain culture. J. Neurophysiol. 79: 1113-1116, 1998. Alterations of synaptic excitation induced by exposure to γ-aminobutyric acid-A (GABAA) receptor antagonists were investigated employing tight-seal whole cell recording from single neurons or pairs of neurons in rat embryonic midbrain culture. Application of GABAA receptor antagonists led to sustained depolarizations followed by synchronous paroxysmal depolarization shifts (PDSs). PDSs induced a transient increase in miniature excitatory postsynaptic currents in the presence as well as in the absence of a N-methyl-d-aspartate receptor antagonist. The increase in glutamate release supports the excitatory drive required to reinitiate PDSs from the quiescent interburst intervals. After washout of GABAA receptor antagonists, synaptic activity remained grouped, regardless of the presence or absence of PDS blockade by tetrodotoxin (TTX). Impediment of action potential-triggered transmitter release by Cd2+ or TTX also induced grouped activity. We conclude that changes in synaptic excitation are produced by the impaired GABAA inhibition per se and by the initiation of PDSs.